Still Elusive - Pd(II)-Mediated Base Pairing by an Acetophenone Oxime Palladacycle within N-15-Labelled Double-Helical Oligonucleotides - Toiviala Maaret; Kleemola Vesa; Maity Sajal; Lönnberg Tuomas (WILEY-V C H VERLAG GMBH, 2025)
Both α and β anomers of an acetophenone C-nucleoside were synthesized and incorporated in the middle of short oligodeoxynucleotides. The ketone oligonucleotides were converted to 15N-labelled oxime oligonucleotides by treatment with 15N-hydroxylamine and, finally, cyclopalladated by treatment with lithium tetrachloropalladate. Comparison of the UV melting profiles of duplexes bearing the β anomer of either the palladacyclic or the metal-free oxime C-nucleoside suggested formation of a stable Pd(II)-mediated base pair, especially with adenine or thymine as the base pairing partner. Melting profiles of the corresponding duplexes bearing the α anomer were much more convoluted, precluding meaningful comparison. 15N NMR spectra were obtained for the β anomeric oxime oligonucleotide as well as its palladacyclic derivative but the signals unfortunately diminished below detection limit when the latter was hybridized with a complementary strand placing a 15N3-labelled thymine opposite to the palladacyclic residue.